Evaluation Methods of Vertical Subgrade Reaction Modulus and Rotational Resistance Moment for Seismic Design of Embedded Foundations - Nagao, T.; Tsutaba, R. (Engineering, Technology & Applied Science Research, 2021)
In a seismic design of embedded foundations, the vertical Subgrade Reaction (SR) acting on a foundation bottom surface and the Rotational Resistance Moment (RRM) generated by the SR are calculated using an SR Modulus (SRM). The SRM and RRM depend on both ground rigidity and Foundation Width (FW). However, the SRM and RRM calculation methods adopted in design codes might not properly consider their FW dependency. In this study, SRM and RRM evaluation methods for embedded foundations subjected to a seismic load were examined by conducting a two-dimensional finite element analysis under the condition where ground rigidity and FW were changed considering the nonlinearity of the ground. The results show that when the seismic load is large and the nonlinearity of the ground appears, the SR distribution is different from the assumption in the design code. The FW dependency of the SRM was lower than the assumption of the design code. Furthermore, methods to calculate the SRM and RRM in accordance with the FW and ground rigidity are proposed.